UPAYA PENINGKATAN KUALIFIKASI AKADEMIS DAN KOMPETENSI GURU AGAMA ISLAM PADA SEKOLAH-SEKOLAH RSBI DI KOTA METRO - Abidin, Zainal (P3M STAIN Jurai Siwo Metro, 2012)
AbstractRSBI is project to empowering the of educational institution, especially in the medium gradeÂ school with international standart. SomeÂ students know thatâsÂ program have available for them to increasing their skills like Â any competitive advantages and comparative advantages, afther they graduated from teaching and learning process on the international standart school. But until now the establishment ofÂ many internationals school still have some problems, like in theÂ funding, management, quality andÂ the otherÂ problems . In Metro City Â thatâs really problems so that many school Â Â especially in Islamic teaching or Islamic instructional, for religions teacher,Â RSBI is the challenge for the to increasing their competence, for example the problem of instructional comtptence because RSBI needs some aspect of teacherâs competence like the English language, and information technology. For Islamic teacher that is become the problem because they must be prepared them to be qualified theacher in international school.Key Word: Â RSBI and Religon instructional, academic competence and qualified of education.